Equitable post-COVID-19 housing delivery: a practical framework to integrate sustainable development goals in Malaysia’s low-cost housing provision - Ebekozien, Andrew; Hafez Ahmed, Mohamed Ahmed; Aigbavboa, Clinton; Samsurijan, Mohamad Shaharudin; Adekunle, Samuel Adeniyi; Akinradewo, Opeoluwa; Said, Mohd Zulhafiz; Noor Azazi, Noor Alyani (EnPress Publisher, 2024)
Studies show that the COVID-19 crisis may threaten to attain sustainable development goals connected with shelter in developing countries, including Malaysia. Low-cost housing provision has been identified as one tool for achieving sustainability goals via synergistic operations. However, studies about post-COVID-19 housing and sustainable development goals integration are scarce in Malaysia. The study investigated the state of post-COVID-19 housing and developed a framework to integrate Goals in housing provision in Malaysia. The study covered four major cities in Malaysia via qualitative research to achieve the study’s objectives. The researchers engaged forty participants via semi-structured virtual interviews, and saturation was achieved. The study utilized a thematic analysis for the collated data and honed them with secondary sources. Findings show that COVID-19 reduced the possibility of low-income earners becoming homeowners. This is because the low-income groups were real losers of COVID-19 economic changes. Also, findings reveal that achieving four Goals from the 17 Goals will improve housing provision in Malaysia’s post-COVID-19 era. The study encourages key housing stakeholders to improve housing delivery, especially for the low-income earners across Malaysia in the post-COVID-19 era. This will imply contributing to achieving four Goals because of the correlation, as part of the study’s implications. © 2024 by author(s).